Strategi Perencanaan Pemasaran Dalam Meningkatkan Penjualan Umkm Kerajinan Tangan Buket Bunga “Edelweiss” - Lina Suryani; Suwandi (CV. ITTC INDONESIA, 2025)
Micro, Small, and Medium Enterpriss (MSME) that produce handcrafted flower bouquets have great potential for growth, but are often hampered by a lack of understanding and implementation of effective marketing strategies. This community service journal aims to present a comprehensive guide to marketing planning strategies that can be implemented by MSME producing edelweiss flower bouquets to increase sales and competiviness. The materials discussed include market analysis, target market determination, product development, pricing, promotion and distribution strategies. It is hped that this journal can serve as a pratical reference for one of the MSME producing edelweiss flower bouquets in designing and implementing their marketing efforts.